P3_1 What’s Popping in the Nuclear Apocalypse? - Chatwin, Oliver; Holtom, Josh; Iorga, Adriana; Tyler, Saffron (Physics Special Topics, 2020)
We investigate the amount of popcorn that could be popped using the energy of all the nuclear weapons in the world. It is found that the energy required to pop on kernel of corn is 0.05099J, and therefore that the energy released by such an explosion would be sufficient to pop 5.072 · 1019 kernels, or 6.898 · 1020kg of corn.